Supraglottic devices as alternative equipment to airway management in state of sudden cardiac arrest - Rafał Czyż; Mateusz Zawłodzki; Izabela Czyż (Kazimierz Wielki University, 2017)
Effective airway management of patient in sudden cardiac arrest is a priority of rescue team on the accident spot. Endotracheal intubation which requires great experience and training is still regarded as the gold standard. Therefore supraglottic airway devices, as alternative devices for airways management are matter greatly role especially in emergency medicine. The aim of this study was to present chosen alternative methods of airway management to patient in sudden cardiac arrest with particular reference to laryngeal mask, I-gel and laryngeal tube. All of supraglottic devices are characterized by easiness in applying without experience in use them. Additionally time need to airway management in use of them is many times shorter than with traditional endotracheal intubation. Fundamental defect in these devices is a fact that they don't provide total safety before aspiration for chime. Current literature shows us that supraglottic airway devices are perfect alternative to endotracheal intubation.